Site-Specific Insertion Polymorphism of the MITE Alex-1 in the Genus Coffea Suggests Interspecific Gene Flow. (27th September 2011) - Dubreuil-Tranchant, Christine; Guyot, Romain; Guellim, Amira; Duret, Caroline; de la Mare, Marion; Razafinarivo, Norosoa; Poncet, Valérie; Hamon, Serge; Hamon, Perla; de Kochko, Alexandre
Abstract : Miniature Inverted-repeat Transposable Elements (MITEs) are small nonautonomous class-II transposable elements distributed throughout eukaryotic genomes. We identified a novel family of MITEs (named Alex ) in the Coffea canephora genome often associated with expressed sequences. The Alex-1 element is inserted in an intron of a gene at the CcEIN4 locus. Its mobility was demonstrated by sequencing the insertion site in C. canephora accessions and Coffea species. Analysis of the insertion polymorphism of Alex-1 at this locus in Coffea species and in C. canephora showed that there was no relationship between the geographical distribution of the species, their phylogenetic relationships, and insertion polymorphism. The intraspecific distribution of C. canephora revealed an original situation within the E diversity group. These results suggest possibly greater gene flow between species than previously thought. This MITE family will enable the study of the C. canephora genome evolution, phylogenetic relationships, and possible gene flows within the Coffea genus.